CO2 Reforming of Biomass Gasification Tar over Ni-Fe-Based Catalysts in a DBD Plasma Reactor - Bianbian Gao; Guoqiang Cao; Yutong Feng; Yuting Jiao; Chunyu Li; Jiantao Zhao; Yitian Fang (Molecules, 2025)
The removal of tar and CO2 represents a critical challenge in the production of biomass gasification syngas, necessitating the development of advanced catalytic systems. In this study, plasma-enhanced catalytic CO2 reforming was employed to remove biomass tar, with toluene selected as a model compound for biomass tar. Supported Nix-Fey/Al2O3 catalysts, with varying Ni/Fe molar ratios (3:1, 2:1, 1:1, 1:2, and 1:3), were synthesized for the CO2 reforming of toluene in dielectric barrier discharge (DBD) non-thermal plasma reactors. The experiments were conducted at 250 °C and ambient pressure. The effects of various Ni/Fe molar ratios, discharge powers, and CO2 concentrations on DBD plasma-catalytic CO2 reforming of toluene to synthesis gas were analyzed. The results indicate that CO and H2 are the primary gaseous products of toluene decomposition, with the selectivity for these gaseous products increasing with the discharge power. Increasing discharge power leads to a higher selectivity for CO and H2 production. A CO2/C7H8 ratio of 1.5 was found to effectively enhance the catalytic performance of the system, leading to the highest toluene conversion and syngas selectivity. The selectivity of the Nix-Fey/Al2O3 catalysts for H2 and CO follows the following order: Ni3-Fe1/Al2O3 > Ni2-Fe1/Al2O3 > Ni1-Fe1/Al2O3 > Ni1-Fe2/Al2O3 > Ni1-Fe3/Al2O3. Notably, the Ni3-Fe1/Al2O3 catalyst exhibits a high CO2 adsorption capacity due to its strong basicity, demonstrating significant potential for both tar conversion and carbon resistance.